До питання розвитку критичного мислення студентів при вивченні математики - Швай, Ольга (Східноєвропейський національний університет імені Лесі Українки, 2019)
Актуальність теми дослідження. Стаття присвячена актуальній проблемі формування критичного мислення студентів. Наголошується на важливості розвитку критичного мислення студентів для підготовки високоосвічених, конкурентоспроможних на ринку праці спеціалістів. Мета і методи дослідження. Метою статті є обґрунтування методичних прийомів формування критичного мислення студентів за допомогою сучасного підручника математики. Методи дослідження– аналіз навчально-методичної літератури в контексті дослідження; вивчення та узагальнення передового педагогічного і власного досвіду роботиу виші. Апробація запропонованих методичних прийомів здійснювалася із застосуванням методів організації педагогічного експерименту в реальних умовах освітнього процесу факультету інформаційних систем фізики та математики СНУ імені Лесі Українки.Оцінювання навчальних досягнень студентів здійснювалося за допомогою методів педагогічного спостереження, анкетування та діагностичних завдань. Результати роботи та ключові висновки. Здійснено термінологічний аналіз поняття «критичнемислення». Окреслено якості та уміння, які необхідно розвивати у студентів для вироблення у них критичного мислення. Увагу акцентовано на тому, що навчальні дисципліни, які читаються на першому курсі, повинні бути не лише джерелом навчальних відомостей, але й засобом формування критичного мислення студентів. Виділено деякі методичні прийоми, які допомагають цілеспрямовано формувати у студентів потреби і мотиви самоаналізу навчальної діяльності. Показано, що сучасні підручники (посібники) повинні стимулювати студентів до активного мислення через відбір змісту навчального матеріалу (системність, новизна, наукова і практична цінність, зв'язок із сучасністю) та через їх структуру. Зазначено, щоактивізувати мислення студентів можна за допомогою демонстрації правильних розумових і практичних дій; фрагментів навчального матеріалу, які стимулюють студентів до осмислення міркувань з різних кутів зору; коментарів і позначок, що орієнтують студентів у логіці розгортання доведень. Встановлено, щопідручник, який містить достатню кількість вправ та задач для самостійного розв'язання, розширює можливості індивідуалізації навчання. При цьому важливим є варіативний добір задач (різні рівні складності; повна, надлишкова, неповна інформація; практично-орієнтовані завдання тощо). Relevance of the research topic. The article analyzes opportunities of developing students’ critical thinking skills, that is a crucial condition for training highly qualified specialists who are capable of continuous self-development, creative use of obtained knowledge and innovative activities. Purpose and methods. The purpose of the article is to substantiate certain methodical methods of developing students’ critical thinking skills using a modern mathematics textbook. Methods of the research are: analysis of educational-methodical literature in a context of the research; learning and generalizing advanced pedagogical and own experience in higher education. An approbation of the proposed methodical techniques was carried out using methods of organization of pedagogical experiment in real conditions of the educational process in the faculty of information systems, physics and mathematics of the Lesya Ukrainka East European National University (100 students of 1-5 courses). Evaluation of students’ educational achievements was carried out using methods of pedagogical observation, questionnaires and diagnostic tasks. Results and key conclusions. The analysis of psycho-pedagogical research leads us to the conclusion that the process of developing students’ critical thinking skills is multifaceted. Development of students' critical thinking skills is a task of all the educational disciplines within educational program, and it should be carried out from the first course. Teacher should conduct a harmonic, diligent work during lectures, practical lessons, individual lessons, etc. Producing a modern methodological support for students’ independent work is the relevant issue nowadays, in particular, preparation of textbooks. Textbooks (manuals) should stimulate students to work independently through selection of a content of educational material (methodology, novelty, scientific and practical value, connection with modernity) and through their structure. The main text of the textbook should contribute to an effective development of student’ thinking skills, provide new information in a context of previously acquired knowledge. Presentation of theoretical material should begin with a statement of problem situations. To activate students' thinking one could also use demonstration of correct mental and practical actions; fragments of educational material that stimulate students to comprehend them from different points of view; comments and tags that orient students in a logic of deployment considerations. It is important to include in the textbook a demonstration of techniques for systematization, algorithmization of educational information that is directly related to the generalization of concepts, methods, the establishment of relationships, etc. Note, that diagrams, drawings, reference schemes that reflect the relations between concepts, show the progress of speculations, etc., will help to provide visualization for a hidden process of thinking. The textbook that contains sufficient number of exercises and tasks for self-solution expands opportunities for individualization of training. Herewith, a variational selection of tasks is important (different levels of complexity, complete, redundant, incomplete information, practical-oriented tasks, etc.). We assume that it is obligatory to include in the textbook correct answers for tests, answers and hints for exercises given for self-solution. These actions will promote development of reflection, a kind of students’ mental activity which is aimed at analysis, comprehension, rethinking of processes and results of their own learning activities. The methodical methods that are substantiated in the article for development of students’ critical thinking skills using the modern mathematics textbook were tested during teaching the disciplines "Discrete mathematics", "Combinatorical problems and complexity of calculations", for which the author wrote corresponding manuals.
Keywords: мислення; thinking; критичне мислення; підручник; critical thinking; textbook